1989
DOI: 10.1111/j.1745-4557.1989.tb00308.x
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Sensory Properties of Beef as Affected by Sex Condition, Muscle and Postmortem Aging

Abstract: The longissimus (LD), biceps femoris (BF), psoas major (PM), semitendinosus (ST) and semimembranosus ( S M ) muscles from 8 bulls and 8 steers were removed from sides at I day postmortem and 7 days postmortem. The sensory and textural properties were evaluated and related to meat composition, meat characteristics and mineral content. Muscles were ranked in order of increasing sensory tenderness ratings: PM>ST>LD>BF>SM. The amount of intramuscular fat was found to be positively correlated to sensory panel tende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…We have shown that shortened and unshortened muscle go through similar proteolysis and tenderization. The lack of tenderization during aging in the psoas major that has been reported by others (Koohmaraie et al, 1988;Seideman et al, 1989) did not occur in this experiment, although less tenderization occurred in the psoas major than in the longissimus. However, this result may simply be due to the fact that the long sarcomeres in psoas major make it so tender that it has little room for improvement.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…We have shown that shortened and unshortened muscle go through similar proteolysis and tenderization. The lack of tenderization during aging in the psoas major that has been reported by others (Koohmaraie et al, 1988;Seideman et al, 1989) did not occur in this experiment, although less tenderization occurred in the psoas major than in the longissimus. However, this result may simply be due to the fact that the long sarcomeres in psoas major make it so tender that it has little room for improvement.…”
Section: Discussionsupporting
confidence: 63%
“…This difference in the toughening effect of shortening among muscles may be partially explained by the results of Dutson et al (1976), who reported that shortening causes a greater reduction in tenderness in muscles with higher connective tissue content. Thus, the higher connective tissue content of longissimus relative to psoas major (Boccard, 1981;Seideman et al, 1989) may partially explain the difference in tenderness at the same sarcomere length.…”
Section: Discussionmentioning
confidence: 99%
“…Changes on-farm, pre-slaughter, post-slaughter processing factors and other man-made factors such as electric stimulus account for the environmental contribution. Factors originated from the muscle also contribute to meat tenderness, such as intermuscular variation, sensitivity of muscle structural proteins to proteolysis, the distribution of muscular connective tissue and sarcomere length ( Koohmaraie et al, 1988 ; Seideman et al, 1989 ; Wheeler and Koohmaraie, 1999 ). A range of studies have shown that postmortem factors, particularly temperature and sarcomere length could determine pre-rigor and proteolysis and affect the conversion of muscle to meat ( Taylor et al, 1995 ; Koohmaraie et al, 1996 ; Roberts et al, 1996 ; Gollasch and Nelson, 1997 ; Hwang et al, 2003 ; Koohmaraie and Geesink, 2006 ).…”
Section: Meat Tendernessmentioning
confidence: 99%
“…Purchas and Barton (1976) reported that beef from Jersey steers was superior in tenderness compared with other breeds. Marbling is highly correlated to sensory tenderness ratings (Seideman et al, 1998), juiciness, and beef flavor (Platter (NRC, 1996). et al, 2003).…”
Section: Introductionmentioning
confidence: 98%